Haunted Memory, Trauma, and Recovery in Louise Erdrich’s The Stone - Alfian Maulana; Faruk Faruk (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
While the ghost is almost always connected with the source of terror, psychological disorder, traumatic memory, unfinished task, or dormant desire, could it also be a guide to collective memory and recovery, especially for Native American society? This study aimed to read the haunting phenomenon in Louise Erdrich’s The Stone as literary work that could give a deeper understanding of the relation among haunting, collective memory, trauma, and recovery. It answered two questions: 1) How the haunting narrated past collective memory and system of power to the living, and 2) How the relationship between the memory and the present living might establish recovery. To analyze the text, this study used the haunting theory by Avery Gordon. The main data was collected from Louise Erdrich’s The Stone. The result revealed that 1) the haunting in this work was related to the demand of Ojibwe memory in the reservation era, that was the demand to be remembered; 2) the traumatic event was not over and continues to occur in the present, and 3) this text developed new mode of practicing testimony through the act of remembrance of the past collective memory.